Evaluation of the Effect of Tissue Compression on the Results of Shear Wave Elastography Measurements. (November 2018) - Vachutka, Jaromir; Sedlackova, Zuzana; Furst, Tomas; Herman, Miroslav; Herman, Jan; Salzman, Richard; Dolezal, Ladislav
Shear wave imaging is considered to be more precise and less operator dependent when compared with strain imaging. It enables quantitative and reproducible data (Young's modulus of the imaged tissue). However, results of shear wave imaging can be affected by a variety of different factors. The aim of this study is to evaluate the effect of the pressure applied by the ultrasound probe during examination on the measured values of Young's modulus. The effect of the tissue compression on the results of the real-time shear wave elastography was evaluated via the gelatine phantom measurements, via the ex vivo experiments with pig liver, and via the in vivo measurements of the thyroid gland stiffness on healthy volunteers. The results of our measurements confirmed that the measured value of Young's modulus increases with the increasing pressure applied on the imaged object. The highest increase was observed during the ex vivo experiments (400%), and the lowest increase was detected in the case of the phantom measurements (8%). A two- to threefold increase in Young's modulus was observed between the minimum and maximum pressure in the case of the in vivo elastography measurements of thyroid gland. The Veronda-Westman theoretical model was used for the description of the tissue nonlinearity. We conclude that tissue compression by the force exerted on the probe can significantly affect the results of the real-time shear wave elastography measurements. Minimum pressure should be used when measuring the absolute value of Young's modulus of superficial organs.